An entry to 2-(cyclobut-1-en-1-yl)-1H-indoles through a cyclobutenylation/deprotection cascade. Issue 18 (22nd April 2021) - Natho, Philipp; Yang, Zeyu; Allen, Lewis A. T.; Rey, Juliette; White, Andrew J. P.; Parsons, Philip J.
Abstract : A transition-metal-free methodology for the synthesis of 2-(cyclobut-1-en-1-yl)-1 H -indoles through a cyclobutenylation/deprotection cascade was developed and the underlying mechanism was studied. Abstract : A transition-metal-free strategy for the synthesis of 2-(cyclobut-1-en-1-yl)-1 H -indoles under mild conditions is described herein. A series of substituted 2-(cyclobut-1-en-1-yl)-1 H -indoles are accessed by a one-pot cyclobutenylation/deprotection cascade from N -Boc protected indoles. Preliminary experimental and density functional theory calculations suggest that a Boc-group transfer is involved in the underlying mechanism.